2019
DOI: 10.1172/jci.insight.125334
|View full text |Cite
|
Sign up to set email alerts
|

Non–fibro-adipogenic pericytes from human embryonic stem cells attenuate degeneration of the chronically injured mouse muscle

Abstract: Conflict of interest: A patent application (30435.354-US-P2) has been filed by BP, FAP, and AD on a method for generation of therapeutic pericytes from human pluripotent stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 49 publications
4
22
0
Order By: Relevance
“…Infraspinatus and supraspinatus muscles were separately fixed in 4% formalin, embedded in paraffin and sectioned axially. Sections were stained with hematoxylin and eosin (H&E) for general tissue structure analysis, measurement of myofiber cross-section 20…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Infraspinatus and supraspinatus muscles were separately fixed in 4% formalin, embedded in paraffin and sectioned axially. Sections were stained with hematoxylin and eosin (H&E) for general tissue structure analysis, measurement of myofiber cross-section 20…”
Section: Histologymentioning
confidence: 99%
“…Experimental RC tears in rats and mice involving the transection of supraspinatus and infraspinatus tendons (TT) along with the suprascapular nerve (DN) have replicated the marked degenerative fibrosis and fat accumulation found in these patients 11–13 . The rodent model of massive RC tears has been used by researchers to study the pathological progression of the disease and to improve their understanding of the cellular response 13–15 to injury, the molecular pathways that are responsible for it 16–18 and test therapeutic approaches to attenuate the progression of muscle degeneration 19–23 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have implicated PDGFRα + FAPs in fibroadipogenesis following massive rotator cuff tears (20,(26)(27)(28)(29)(30)(31). Liu et al demonstrated significant co-localization of immunofluorescence signals from transgenic murine PDGFRα + cells and adipogenic markers including peroxisome proliferatoractivated receptor γ (PPARγ), adiponectin, and perilipin A following tendon transection plus denervation in a murine rotator cuff tear (RCT) model (20).…”
Section: Contribution Of Rc Faps To Fibro-adipogenesismentioning
confidence: 99%
“…130 Injection of human MSC-like pericytes into degenerating murine RC muscles (tenotomy and neurectomy) also attenuates the level of degeneration. 131 Furthermore, beneficial effects of MSC delivery through paracrine signaling have been documented in other types of skeletal muscle injuries, including crush trauma and volumetric muscle loss, [132][133][134][135][136][137] suggesting the clinical potential of MSC therapy in promoting muscle regeneration in multiple muscle-associated injury and disease contexts.…”
Section: Cell Therapymentioning
confidence: 99%